Intuitionistic fuzzy proximity spaces - Seok Jong Lee; Eun Pyo Lee (International Journal of Mathematics and Mathematical Sciences)
We introduce the concept of the intuitionistic fuzzy proximity as a generalization of fuzzy proximity, and investigate its properties. Also we investigate the relationship among intuitionistic fuzzy proximity and fuzzy proximity, and intuitionistic fuzzy topology.